Estrogen Receptor Function: Impact on the Human Endometrium - Yu, Kun; Huang, Zheng-Yuan; Xu, Xue-Ling; Li, Jun; Fu, Xiang-Wei; Deng, Shou-Long (Frontiers in Endocrinology, 2022)
The physiological role of estrogen in the female endometrium is well established. On the basis of responses to steroid hormones (progesterone, androgen, and estrogen), the endometrium is considered to have proliferative and secretory phases. Estrogen can act in the endometrium by interacting with estrogen receptors (ERs) to induce mucosal proliferation during the proliferative phase and progesterone receptor (PR) synthesis, which prepare the endometrium for the secretory phase. Mouse knockout studies have shown that ER expression, including ERα, ERβ, and G-protein-coupled estrogen receptor (GPER) in the endometrium is critical for normal menstrual cycles and subsequent pregnancy. Incorrect expression of ERs can produce many diseases that can cause endometriosis, endometrial hyperplasia (EH), and endometrial cancer (EC), which affect numerous women of reproductive age. ERα promotes uterine cell proliferation and is strongly associated with an increased risk of EC, while ERβ has the opposite effects on ERα function. GPER is highly expressed in abnormal EH, but its expression in EC patients is paradoxical. Effective treatments for endometrium-related diseases depend on understanding the physiological function of ERs; however, much less is known about the signaling pathways through which ERs functions in the normal endometrium or in endometrial diseases. Given the important roles of ERs in the endometrium, we reviewed the published literature to elaborate the regulatory role of estrogen and its nuclear and membrane-associated receptors in maintaining the function of endometrium and to provide references for protecting female reproduction. Additionally, the role of drugs such as tamoxifen, raloxifene, fulvestrant and G-15 in the endometrium are also described. Future studies should focus on evaluating new therapeutic strategies that precisely target specific ERs and their related growth factor signaling pathways.